Effects of Mountain Uplift and Climatic Oscillations on Phylogeography and Species Divergence in Four Endangered Notopterygium Herbs - Shahzad, Khurram; Jia, Yun; Chen, Fu-Lin; Zeb, Umar; Li, Zhong-Hu (Frontiers in Plant Science, 2017)
Mountain uplift and climatic fluctuations are important driving forces that have affected the geographic distribution and population dynamics history of organisms. However, it is unclear how geological and climatic events might have affected the phylogeographic history and species divergence in high-alpine herbal plants. In this study, we analyzed the population demographic history and species differentiation of four endangered Notopterygium herbs on the high-altitude Qinghai–Tibetan Plateau (QTP) and adjacent areas. We combined phylogeographic analysis with species distribution modeling to detect the genetic variations in four Notopterygium species (N. incisum, N. franchetii, N. oviforme, and N. forrestii). In total, 559 individuals from 74 populations of the four species were analyzed based on three maternally inherited chloroplast fragments (matK, rbcL, and trnS-trnG) and one nuclear DNA region (internal transcribed spacer, ITS). Fifty-five chloroplast DNA (cpDNA) and 48 ITS haplotypes were identified in the four species. All of the cpDNA and ITS haplotypes were species-specific, except N. franchetii and N. oviforme shared one cpDNA haplotype, H32. Phylogenetic analysis suggested that all four species formed a monophyletic clade with high bootstrap support, where N. franchetii and N. oviforme were sisters. In addition, each Notopterygium species generated an individual clade that corresponded to their respective species in the ITS tree. Population dynamics analyses and species distribution modeling showed that the two widely distributed herbs N. incisum and N. franchetii exhibited obvious demographic expansions during the Pleistocene ice ages. Molecular dating suggested that the divergence of the four Notopterygium species occurred approximately between 3.6 and 1.2 Mya, and it was significantly associated with recent extensive uplifts of the QTP. Our results support the hypothesis that mountain uplift and Quaternary climatic oscillations profoundly shaped the population genetic divergence and demographic dynamics of Notopterygium species. The findings of this and previous studies provide important insights into the effects of QTP uplifts and climatic changes on phylogeography and species differentiation in high altitude mountainous areas. Our results may also facilitate the conservation of endangered herbaceous medicinal plants in the genus Notopterygium.